Biological Hazards in Food - Rosanna Tofalo (Frontiers Research Topics, 2017)
The ingestion of food containing pathogenic microorganisms (i.e. bacteria and their toxins, fungi, viruses) and parasites can cause food-borne diseases in humans. A growing number of emerging pathogens, changes of virulence of known pathogens and appearance of antibiotic resistance has recently exposed consumers to a major risk of illness. Also infected people and the environment can spread microorganisms on raw or processed food. Outbreaks of food-borne diseases are often unrecognized, unreported, or not investigated and particularly in developing countries their agents and sources are mostly unknown. Surveillance and analytical methods aiming at their detection are to be hoped, as well as good strategies to struggle against these threats. This E-book is subdivided in chapters regarding to pathogenic and spoiling microorganisms, chemical hazards produced by biological agents and food safety management systems.